2003
DOI: 10.1097/01.tp.0000084308.19565.2b
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent functional nuclear factor of activated T cell 1 mRNA and protein expression in cord blood and adult T cells

Abstract: Cord blood (CB) cells are now an important source of stem cells for bone marrow reconstitution as a result of the decreased risk of graft-versus-host disease that was attributed to previously reported absent or diminished nuclear factor of activated T (NFAT) cell 1 expression by CB T cells. This study reexamines NFAT1 expression in CB T cells. CB T cells were examined for NFAT1 mRNA and protein expression. These cells were then stimulated, and NFAT1 translocation and interleukin-2 production were assessed. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In contrast, O’Neill et al . [38] reported similar levels of NFAT‐1 in resting or activated neonatal and adult CD4 T cells. The basis of these conflicting results remains unclear.…”
Section: In Vitro Studies Of Human Neonatal T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, O’Neill et al . [38] reported similar levels of NFAT‐1 in resting or activated neonatal and adult CD4 T cells. The basis of these conflicting results remains unclear.…”
Section: In Vitro Studies Of Human Neonatal T Cellsmentioning
confidence: 99%
“…Contain high concentrations of TRECs [10,11] High cell turn-over [10][11][12][13][14] Have high constitutive telomerase activity and long telomeric sequences [10] Have increased susceptibility to apoptosis, prevented by cytokines signalling through the IL-2 receptor g -chain [11,14,16] Proliferation induced by IL-7 and IL-15 [10,11,13,14,16,17,19,20] Low production of IFN-g by CD4 T lymphocytes associated with hypermethylation of IFN-g promoter [25,26,28] Expression of CD40 ligand by CD4 T lymphocytes is controversial [29][30][31][32][33][34][35] Expression of NFAT by CD4 T lymphocytes is controversial [36][37][38] CD25 + regulatory T lymphocytes occur spontaneously during foetal life [41][42][43][44] and previously been proposed as a marker of recent thymic emigrants [40]. Essential regulatory mechanisms controlling T cell responses are in place in early life.…”
Section: Referencesmentioning
confidence: 99%
“…We observed that both Smad3 and NFATc2 serum levels were significantly higher in RA patients than in healthy subjects, reflecting the ongoing inflammatory process in patients and the attempts to keep it under control. Several previous reports have described Smad3 or NFATc2 mRNA and/or protein levels , but our report is the first, to our knowledge, to explore the protein expression of both in the peripheral blood of RA patients. We observed that RA patients had significantly higher Smad3 and NFATc2 protein levels than controls, but we found no correlation between both protein levels and clinical parameters and examined SNPs.…”
Section: Discussionmentioning
confidence: 81%
“…The transcriptome and epigenetic profiles, along with functional readouts from cord blood and adult naïve CD8 + T cells, corroborated that neonatal CD8 + T cells are more innate-like by displaying, among others, less cytotoxic functions, while being more prone toward producing antimicrobial peptides and reactive oxygen species (ROS) (24). It is not clear if costimulatory capacity through CD40 ligand on T cells is defective (25)(26)(27), or if a differential activity of the transcription factor NFAT (28), which affects T-cell costimulatory capacity and IFN-γ production, is present during early childhood years.…”
Section: The Human T Cell Compartment At Different Agesmentioning
confidence: 99%